Respiratory mechanics and morphometric changes during anesthesia with ketamine in normal rats - O. Alves-Neto; P. Tavares; P.R.M. Rocco; W.A. Zin (Brazilian Journal of Medical and Biological Research, 2001)
Ketamine is believed to reduce airway and pulmonary tissue resistance. The aim of the present study was to determine the effects of ketamine on the resistive, elastic and viscoelastic/inhomogeneous mechanical properties of the respiratory system, lungs and chest wall, and to relate the mechanical data to findings from histological lung analysis in normal animals. Fifteen adult male Wistar rats were assigned randomly to two groups: control (N = 7) and ketamine (N = 8). All animals were sedated (diazepam, 5 mg, ip) and anesthetized with pentobarbital sodium (20 mg/kg, ip) or ketamine (30 mg/kg, ip). The rats were paralyzed and ventilated mechanically. Ketamine increased lung viscoelastic/inhomogeneous pressure (26%) compared to the control group. Dynamic and static elastances were similar in both groups, but the difference was greater in the ketamine than in the control group. Lung morphometry demonstrated dilation of alveolar ducts and increased areas of alveolar collapse in the ketamine group. In conclusion, ketamine did not act at the airway level but acted at the lung periphery increasing mechanical inhomogeneities possibly resulting from dilation of distal airways and alveolar collapse.